Making roundness measurement applications and control systems on the Roundness Tester Machine - Dodi Sofyan Arief; Eko Jadmiko; Adhy Prayitno; Muftil Badri; M. Dalil (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2019)
Dial indicator is a comparison device usually used in industrial activities, especially in production. To make measurements at this time must be supported by technology that can facilitate operators when using it and when analyzing measurement results. Involving the programme and microcontroller are a solution to developing in roundness measurement, and then the results can be more accurate or thorough between the readable values read from the measuring instrument with the actual value of varying the amount of data. Roundness application is a program that can input measurement data automatically and can do calculations directly. Then, it can display a reference circle, a table that calculates the values of X, Y, R, X’, Y’, R’, Roundness Deviation, Run out Concentricity or a shift in the center point and also the center point shift or Theta. In measuring roundness, the test object is used the Standard Mandrel which has been certified by PT. Global Quality Indonesia, by determining three points or positions, namely in the first position the amount of data is 180, in the second position the amount of data is 90 and in the third position, the amount of data is 60 with a rotating speed of 15 mm/s. The results of the reference circle can be seen in each calculation in each position, in the second position the roundness deviation values are approaching of the Mandrel.